The winning way 2.0 : Learnings from Sport for Managers - Bhogle, Anita; Bhogle, Harsha (Haryana Business - Penguin Random House, 2022)
On management mantras by way of examples from cricket and corporate world
Keywords: Cricket - Psychological aspects